Islamic Symbolism and Cultural Integration in The Sekaten Ceremony in Yogyakarta - Arroisi, Jarman; Kamil, Rizvan Falah; Shalahudin, Henri; Amrullah, Khasib (Prodi Studi Agama-Agama, 2025)
The Sekaten ceremony in Yogyakarta has been preserved for centuries as part of the commemoration of the Prophet Muhammad’s birth. This study analyzes how three central rituals of the Sekaten, namely Miyos Gongso, Miyos Dalem, and Grebeg Mulud, function as symbolic media for transmitting Islamic devotion, ethical guidance, and communal solidarity through Javanese cultural forms. The research applies a qualitative descriptive approach with a phenomenological and symbolic framework. Data are based on textual and historical sources that document Islamic acculturation and ritual practice. The analysis employs hermeneutic interpretation supported by triangulation of data and theory as well as interpretative phenomenological analysis to strengthen credibility and depth of interpretation. The findings show that Miyos Gongso conveys Islamic teachings through gendhing compositions that emphasize sincerity, repentance, and purity while remaining embedded in Javanese musical aesthetics. Miyos Dalem presents the Prophet’s biography as a form of ritual pedagogy that promotes ethical emulation and parallels the manaqib tradition. Grebeg Mulud culminates the celebration with gunungan offerings that express gratitude to God, dramatize life’s struggles, and reinforce communal solidarity through shared participation. The study demonstrates that the spread of Islam in Java was achieved not by rejecting existing traditions but by reinterpreting them symbolically. The Sekaten illustrates how Islamic values were embedded in cultural practices, producing a synthesis that remains socially persuasive and spiritually meaningful. This case contributes to scholarship on religion and culture by showing how faith becomes localized through cultural engagement and symbolic negotiation.